2001
DOI: 10.1126/science.1058782
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Carbon Nanotubes and Nanotube Circuits Using Electrical Breakdown

Abstract: Carbon nanotubes display either metallic or semiconducting properties. Both large, multiwalled nanotubes (MWNTs), with many concentric carbon shells, and bundles or "ropes" of aligned single-walled nanotubes (SWNTs), are complex composite conductors that incorporate many weakly coupled nanotubes that each have a different electronic structure. Here we demonstrate a simple and reliable method for selectively removing single carbon shells from MWNTs and SWNT ropes to tailor the properties of these composite nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
1,004
4
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,613 publications
(1,073 citation statements)
references
References 17 publications
37
1,004
4
7
Order By: Relevance
“…17,28 It is worth noting that a value of I on / I off up to 500 can be achieved in such devices, as shown by Seidel et al, 28 after postfabrication treatment, such as selective destruction of metallic SWNTs by high electric field. Also, values as high as 10 5 have been reported by Collins et al, 16 after such modifications to devices with initial I on / I off ratios of ϳ3. Interestingly, our devices consistently show saturation of the output current below V g = −420 mV ͑V on ͒ at all bias voltages ͑V ds ͒.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…17,28 It is worth noting that a value of I on / I off up to 500 can be achieved in such devices, as shown by Seidel et al, 28 after postfabrication treatment, such as selective destruction of metallic SWNTs by high electric field. Also, values as high as 10 5 have been reported by Collins et al, 16 after such modifications to devices with initial I on / I off ratios of ϳ3. Interestingly, our devices consistently show saturation of the output current below V g = −420 mV ͑V on ͒ at all bias voltages ͑V ds ͒.…”
Section: Resultsmentioning
confidence: 61%
“…15 Despite these demonstrated breakthroughs, the progress toward CNT-based electronics has been rather slow due to a lack of ͑a͒ technique͑s͒ to produce pure, isolated semiconducting SWNTs and ͑b͒ a process for an industrially scalable production of useful devices. Since most growth techniques yield a mixture of metallic ͑m͒ and semiconducting ͑sc͒ SWNTs, which are often difficult to separate, ingenious methods such as high electric-fieldinduced destruction 16,17 and chemically modified deactivation 18,19 of m SWNTs have been proposed and utilized to realize sc SWNT devices.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CNTs have current carrying capacities that exceed 10 mA nm À2 because of their strong CÀC bonds, [100] which is much higher than the noble metals ($10 nA nm À2 ). Avouris and coworkers [101,102] first found that when applying a high density current through multiwalled carbon nanotubes (MWNTs), they did not fail by electromigration, but by a layer-by-layer breakdown of individual carbon shells, to eventually result in nanogaps within the nanotubes. This phenomenon was adopted to fabricate nanogap electrodes, called the electrical breakdown method.…”
Section: Electrical Breakdown Of Carbon Nanotubes For Nanogap Electrodesmentioning
confidence: 99%
“…Therefore, nowadays, the CNT separation is widely used, for example, using electrical breakdown [133], chemical reagents [134] and laser or microwave radiation [135]. Though these techniques result in the destruction of removed particles.…”
Section: Cnt Separationmentioning
confidence: 99%